Modeling of biomechanical human body model for seat to head transmissibility analysis. (February 2023) - Bhardawaj, Sono; Sharma, Rakesh Chandmal; Sharma, Sunil Kumar; Gopala Rao, LVV; Vashist, Amit
Under low-frequency excitation, the human subject is highly sensitive to Whole Body Vibrations (WBV). In the present paper, a biodynamic human model is seated posture without backrest support and also with backrest support at different angles (i.e., 0°, 15° and 30°) is formulated to analyse the influences of the frequency and the magnitude of the vibration, backseat support and the angles of inclination of the backseat support on Seat To Head Transmissibility (STHT) of the biodynamic human subject in seating position exposed to WBV. The model parameters such as damping, mass and stiffness of the mathematical model considered in this paper are derived from an alternate methodology which is based on anthropometric data. The STHT is computed analytically with the help of MATLAB software for all the considered cases. The effect of vibration and excitation frequencies on STHT is analysed. The results of STHT evaluated from this work are justified by comparing the same with the mean STHT characteristics reported in past studies and the results of the present analysis come out to be in good agreement with past published research.